EVALUASI PERKEMBANGAN KAWASAN TRANSMIGRASI WILAYAH PAMULUTAN KABUPATEN OGAN ILIR SUMATERA SELATAN - Rudi Subiyakto (Universitas Tribhuwana Tunggadewi, 2022)
The purpose of this study is to present the results of the evaluation of the development of transmigration areas using index numbers. This study uses quantitative methods, especially to determine index numbers. The research data was collected using a questionnaire, the respondents consisted of elements of the government, the private sector, and the community. Respondents gave scores on the questionnaire which was guided directly by the researcher. 150 respondents were divided into 5 groups according to the number of evaluation dimensions. Determination of the index following the technique of multidimensional scaling (MDS). The index results show that the Pamulutan Transmigration Area is included in the category of autonomy. After receiving intervention in several dimensions as a strengthening program for the next 5 years, the area has become a competitive transmigration area. The results showed that the Parit Rambutan area met the autonomy and competitive criteria. Meanwhile, Indralaya and West Pamulutan are still in the undeveloped category. The results of this evaluation become a recommendation for the Ministry of Transmigration to make regulations and intervention actions in the development of transmigration areas for the next 5 years.AbstrakTujuan dari penelitian ini adalah untuk memaparkan hasil evaluasi pengembangan kawasan transmigrasi dengan menggunakan angka indeks. Penelitian ini menggunakan metode kuantitatif, terutama untuk menentukan angka indeks. Pengumpulan data penelitian dilakukan dengan menggunakan kuesioner, responden terdiri dari unsur pemerintah, swasta, dan masyarakat. Responden memberikan skor pada kuesioner yang dipandu langsung oleh peneliti. 150 responden dibagi menjadi 5 kelompok sesuai dengan jumlah dimensi evaluasi. Penentuan indeks mengikuti teknik multidimensional scaling (MDS). Hasil indeks menunjukkan bahwa Kawasan Transmigrasi Pamulutan termasuk dalam kategori otonomi. Setelah mendapat intervensi dalam beberapa dimensi sebagai program penguatan selama 5 tahun ke depan, kawasan tersebut menjadi kawasan transmigrasi yang berdaya saing. Hasil penelitian menunjukkan bahwa kawasan Parit Rambutan memenuhi kriteria otonomi dan kompetitif. Sedangkan Indralaya dan Pamulutan Barat masih dalam kategori belum berkembang. Hasil evaluasi ini menjadi rekomendasi bagi Kementerian Transmigrasi untuk membuat regulasi dan tindakan intervensi dalam pengembangan kawasan transmigrasi untuk 5 tahun ke depan.